INTERNET OF THINGS (IOT) BASED SOLAR RENEWABLE ENERGY INTELLIGENT IRRIGATION SYSTEM WITH ROBOT (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Climate change and the finite nature of traditional electricity  production  sources  have  resulted  in  the  increasing utilization of renewable electricity sources in today’s electricity grid architecture. Which is hoped to eventually lead to a hundred percent   renewable   electricity   grid   architecture.   A    purely renewable electricity grid will bring about the implementation of the Internet of Renewable Energy (IoRE). The European Union (EU) in an attempt to stimulate and strengthen the integration of electricity grid architecture of member states has set in motion several strategies. A great strategy should be a purely renewable electricity grid assets integration in the region. Besides hydro and wind  energy,  bioenergy  is  following  on  the  listing  of  vital renewable energy sources consumed in the European electricity generation   mix.   Bioenergy   electricity   combined   with   other renewables  on  the  IoRE  framework  will  lead  to  a  sustainable electricity grid integration in the EU. The anticipated utilization of IoRE technology in the short-term and long-term in the region will   lead   the   way   to   assess   a   hundred   percent   renewable electricity product by consumers in each member country. It will as well bring about cleaner electricity product production in theEU.